The Slippery Stage of The Square: Deconstructive Performativity in Ruben Östlund’s Films - Kérchy, Vera (Acta Universitatis Sapientiae. Film and Media Studies, 2025)
Ruben Östlund’s socially critical stories cannot be analysed only from a moral point of view. His films also address the theory of deconstructive performativity, questioning the possibility of authenticity and intentional action. Unexpected turns in everyday rituals or spontaneity that exposes and overrides artistic intentions can be treated as allegories of “structural parasitism” (Jacques Derrida, Signature, event, context . Tr. Samuel Weber and Jeffrey Mehlman, Northwestern University Press, Evanston IL, 1988). The derailments of the character’s performative acts reveal the constant possibility of speech act “failure” (John L. Austin, How to do things with words , Harvard University Press, Cambridge, Massachusetts, 1975), exposing the illusory nature of the autonomous subject (Judith Butler Performative acts and gender constitution: an essay in phenomenology and feminist theory. Theatre Journal 1988 40: 19–531. http://www.jstor.org/stable/3207893 . Accessed 23 Feb 2025.). The Square (2017) connects the failure of contemporary art to have a direct socio-political impact with the emptiness of the aesthetics of l’art pour l’art , on the one hand, and the problems of appropriating art as a commodity, on the other. As the artistic intention to impose eventfulness and the intention to rigidify presence into an ideological message fails, deconstructive performativity is revealed anamorphically. This presence, which subverts artistic action through its trace-like appearance, manifests itself as an embarrassing and uncanny experience for both the characters and the viewer.